User Interface Design for the Orca Music Player Mobile Application - Habib, Tamam Aulia; Azly, Rendy; Irza, Muhammad Aulia; Prasetya, Ilham (Tsabit Journal of Computer Science, 2024)
The rapid development in the field of information technology has resulted in a significant change in the way music is listened to. The current digital generation prefers to listen to music online through their digital devices. Thus, designing User Interface and User Experience on Mobile Music Player Applications using the User Centered Design method which consists of Plan the human centered process, Specify the context of use, Specify user and organizational requirements, and Produce design Solution. The target audience for this design is productive age children 15-35 years old with product limitations that only reach the prototype stage and feature services that are still lacking. The platform used is the android and ios mobile platform and UI design by making Wireframe of the application design.